The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/plants10071365
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Induced Activation of the Antioxidant Defense System Counteracts the Adverse Effects of Salinity in Durum Wheat

Abstract: The present study was carried out with the aim of (i) evaluating the effect of chitosan (CTS) on the growth of durum wheat under salinity and (ii) examining CTS-regulated mechanisms of salinity tolerance associated with the antioxidant defense system. To achieve these goals, durum wheat seedlings were treated with CTS at different molecular weight, low (L-CTS, 50–190 kDa), medium (M-CTS, 190–310 kDa) and high (H-CTS, 310–375 kDa). The results obtained show that exposure to 200 mM NaCl reduced the shoot and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…Our experiment showed that the salt stress caused significant increases in TPC in unbiostimulated plants, and this can be seen as a plant response to improve its free radical scavenging activity (Table 3). Therefore, it can be concluded based on TPC results that the biostimulant reduced the stress and, consequently, the TPC in maize [59].…”
Section: Discussionmentioning
confidence: 96%
“…Our experiment showed that the salt stress caused significant increases in TPC in unbiostimulated plants, and this can be seen as a plant response to improve its free radical scavenging activity (Table 3). Therefore, it can be concluded based on TPC results that the biostimulant reduced the stress and, consequently, the TPC in maize [59].…”
Section: Discussionmentioning
confidence: 96%
“…Detoxification of H 2 O 2 by enhancing CAT and POD activity with CHT amendment resulted in increased tolerance of milk thistle plants to salinity [ 65 ]. Foliar application of low- and medium-molecular-weight CHT to durum wheat under salt stress increased the activities of SOD and CAT [ 66 ]. Likewise, SOD, CAT, and POD activities were increased following foliar application of CHT in salt-stressed tomato plants [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cs and CsNPs application improved plant productivity under different stressed conditions by boosting plant immune responses and by the activation of various defense related enzymes and decreasing reactive oxygen species (ROS) of plants (E. F. Ali et al, 2021;Attia et al, 2021;Picchi, Gobbi, Fattizzo, Zefelippo, & Faoro, 2021;Quitadamo, De Simone, Beleggia, & Trono, 2021).…”
Section: Effect Of Cs/csnps On Antioxidant Activitymentioning
confidence: 99%